The physical basis of the twimyo nomo yop chagi test in taekwon-do ITF - Wasik, J. (Archives of Budo, 2007)
Study aim: The aim of this paper is the finding of the optimum conditions for the preforming of the twimyo nomo yop chagi. Allowing the competitor to achieve the best possible results. Material/methods: This paper contains the theoretical description of the test, from the physical point of view. Results: During the special technique test, the height that the competitor successfully completes, is a sum of 3 distances: the distance between the point of takeoff, and the COG, the horizontal distance that the COG overcomes during the flight phase, the distance between the COG and the landing spot. This is shown by the following formula: D= mo + d + ml. The combination of the horizontal speed generated during the run up and the vertical speed obtained during the takeoff determines the angle of takeoff: L = arctan vy /vx Conclusions: After the analysis of this technique we are able to determine the factors that infl uence the distance of the jump. These factors are: the force of the takeoff, takeoff velocity the angle of takeoff. The takeoff velocity is the most important factor, it depends on the velocity during the run up and the change of that velocity during the takeoff. Physics has shown that the best takeoff angle in order to achieve the best distance is 45 degrees. In order to achieve this angle the time of takeoff must be very short and the velocity very high. The perfect combination would be to achieve the maximum velocity and a minimum loss of this velocity during the preparation for the takeoff, and the takeoff itself is to take place in the shortest possible period of time.